PROBLEMS OF TUNGSTEN MINING AND REGENERATION OF ITS WASTE IN UZBEKISTAN - Shonazarova, Shakhnoza; Karimov, Makhmud; Kuchkarova, Noila (University Research Base, 2024)
The shortage of tungsten and high prices for it create a need to increase its production and require the development of technologies with deeper extraction of tungsten. A large number of methods have been proposed to solve these problems. An analysis of industrially used technologies is provided. The results of the work of Almalyk MMC specialists on the creation and implementation of new technologies in production are presented. Thus, for the first time in our country, they developed and implemented a technology for processing tungsten-containing industrial waste from the Ingichka deposit on an industrial scale. As a result of a series of works, the first tungsten product was obtained, for which an international certificate was issued, which made it possible to resume tungsten production based on domestic raw materials. The results of research work on the development of domestic technologies for the reuse of worn-out carbide tools, as well as the regeneration of industrial waste, were discussed.